(untitled) (Homoeopathy for All, 2023)
Polycystic ovary syndrome (PCOS) is a new gynecological epidemic. It is the most common endocrine disorder among women of reproductive age groups 12-45 years. It is thought to be one of the leading causes of female subfertility and the most frequent endocrine problem in women of reproductive age. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of PCOS.